Literatura infantojuvenil para o ensino fundamental e a leitura do Sítio do Pica-pau Amarelo, de Monteiro Lobato - LOBATO, Joelma da Silva (2022)
In developing the theme proposed in this work, we sought to relate the literature on children and adolescents developed by Monteiro Lobato with the development of reading in the context of primary education, because knowing the relevance of the work Lobatina it is possible to apply it through actions in the school context , especially making use of the work The Yellow Woodpecker Site for the encouragement and awakening of reading. Thus, offer practical subsidies for the development and practice of reading, from the work of Monteiro Lobato which is the main focus of the work. In order to reach this proposal, a bibliographical review was carried out of the main authors who approach the issue of reading through Child and Adolescent Literature in the scenario of elementary education, highlighting practical situations that the teacher can use to develop reading. Thus, teachers are offered a subsidy capable of improving their practices in the classroom, both for reading and for a better realization of the teaching-learning process.